Fundamentals Matter: Forecasting the 2020 Democratic Presidential Nomination. Issue 1 (20th January 2021) - Dowdle, Andrew J.; Adkins, Randall E.; Sebold, Karen; Steger, Wayne P.
ABSTRACT: Previous studies used pre-primary variables (e.g., endorsements, national polls, and fundraising) and momentum variables from the Iowa and New Hampshire contests to predict presidential nomination outcomes. Yet, races with no elite favorite and no clear frontrunner in polls, such as in the 2020 Democratic race, are more difficult to forecast. We replicate and extend two forecasting models from 1980 to 2016 used by Dowdle et al. (2016 ) to predict the 2020 results. Our models suggest that Joe Biden may have been a stronger frontrunner than expected but that subsequent models may need to incorporate other early contests, such as the South Carolina primary. Overall, our results also argue that the fundamental factors in winning presidential nominations have remained relatively stable.